THE IMPACT OF REGIONAL ORIGIN INCOME AND ACCOUNTED FUNDS ON THE REGIONAL EXPENDITURE OF THE GOVERNMENT OF THE RIAU ARCHIPELAGO PROVINCE - Sunarto Wage; Wasiman Wasiman; Rahmat Rahmat; Syahril Effendi; Nanda Harry Mardika (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
This study aims to investigate and analyze the impact of Regional Primary Income (PAD) and balance funds on the regional expenditure of the provincial government of Riau Islands for the period 2009 - 2021, so there are 13 data obtained from the Central Bureau of Statistics (BPS). in the province of Riau Islands. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of the simultaneous hypothesis testing that the Regional Initial Income (PAD) and balance funds together have no effect on the regional expenditure of the provincial government of Riau Islands, with a coefficient of determination test result of 43%.